ENT 530 Social Media Portfolio: Nyala / Nuur Najaahtul Nabilah Baharuddin - Baharuddin, Nuur Najaahtul Nabilah (2021)
The main objective that is to achieve for the business is to offer variety of scented candles from Malaysia to our customer with affordable price and luxurious scent. The business was started on October 2020. According to the customer review, the product gave a fantastic feedback as the signature fragrances make the customer remembered the scent. This product is also liked by many due to the cheap and affordable price. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of its opening, Nyala by Kendel.Co was sold more than more than 80 packages for with different scent of Nyala. Increasing demands for our product results into a good profitable sale revenue to our business project. Therefore, Nyala by Kendel.Co is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing.